2011
DOI: 10.1097/pcc.0b013e31820abca8
|View full text |Cite
|
Sign up to set email alerts
|

Very high serum ferritin levels are associated with increased mortality and critical care in pediatric patients

Abstract: In this pediatric population, with serum ferritin levels of >3000 ng/mL, there was increased risk for both receipt of critical care and subsequent death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
66
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 14 publications
6
66
0
3
Order By: Relevance
“…Finally, other causes of ferritin increase, such as iatrogenic iron overload, could not be excluded, but appeared unlikely. Ferritin has recently received growing attention in human medicine as a potential prognostic marker in critical care patients (Bennett et al, 2011). In our study, non-survivors presented a significantly higher ferritin concentration than survivors, suggesting that these animals could have had a more severe APR, or a greater degree of ferritin leakage associated with tissue damage or haemolysis.…”
Section: Discussionmentioning
confidence: 68%
“…Finally, other causes of ferritin increase, such as iatrogenic iron overload, could not be excluded, but appeared unlikely. Ferritin has recently received growing attention in human medicine as a potential prognostic marker in critical care patients (Bennett et al, 2011). In our study, non-survivors presented a significantly higher ferritin concentration than survivors, suggesting that these animals could have had a more severe APR, or a greater degree of ferritin leakage associated with tissue damage or haemolysis.…”
Section: Discussionmentioning
confidence: 68%
“…Third, although the optimal cutoffs derived using the Youden Method add statistical clarity to our study, previous investigators have reported utility with other CRP and ferritin thresholds cutoffs. 310 For example, Seattle Children’s Hospital reported a stepwise risk when ferritin levels reached 1,000 ng/mL or 3,000 ng/mL whereas a Brazilian study noted increased risk at 500 ng/mL. More studies are required to determine the reason for these differences in cutoff values.…”
Section: Discussionmentioning
confidence: 99%
“…12 In a study of all hospitalized children at Seattle Children’s Hospital, ferritin levels > 1,000 ng/mL and > 3,000 ng/mL were associated with a stepwise increase in the risk of subsequent admission to the pediatric intensive care unit or death over the next five years regardless of cancer, rheumatologic disease, or hemolytic anemia status. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Of note, a recent examination of 55 biomarkers in Ebola hemorrhagic fever (EHF) patients indicated that elevations in serum thrombomodulin and serum ferritin were both associated with hemorrhage and mortality 51,52 . Elevation of serum ferritin has been shown to correlate with mortality among pediatric patients with MAS in multiple settings 53,54 .…”
Section: Introductionmentioning
confidence: 99%